The state of ESG in European private equity buyouts: an analysis of GP integration and its link to fund performance-measuring impact in sustainable investments enhacing metrics and compliance for company X sustainable allocation funds - Schneider, Rafael (2025)
This study empirically tests the link between ESG integration and financial performance using a sample of 624 European buyout funds from Preqin. A nuanced GP-level ESG integration score was constructed to move beyond binary labels. While multivariate regressions show no significant overall performance effect, subgroup analysis reveals a strong, negative association between ESG commitment and realized returns for liquidated and early-vintage funds. These findings indicate the ESG-performance relationship in private equity is not uniform but highly context-dependent, with traditional drivers like fund size and GP scale remaining dominant predictors of performance.